THEME AND THEMATIC PROGRESSION OF UNDERGRADUATE THESIS: INVESTIGATING MEANING MAKING IN ACADEMIC WRITING - Gunawan, Wawan; Aziza, Fatayatul (Universitas Pendidikan Indonesia, 2017)
This study attempts to investigate the choice of theme and thematic progression deployed in one of the considerably best undergraduate theses in a university in Indonesia. The choice of theme and thematic progression is constrained by the audience of a particular culture; therefore, the process of meaning making is culturally situated. The university, in effects, has its standard for grading academic writing, representing a culture that shapes meaning making processes. This study particularly focuses on how theme and thematic progression contributes to making meanings to meet the demands of the institution. This study employs a descriptive-qualitative research design embracing the characteristics of a case study approach. The data obtained from the best undergraduate studentâ€™s thesis were analyzed from the perspective of Hallidayâ€™s theme system and its progression. The analysis shows that the three types of theme: topical, interpersonal and textual themes, were realized in the thesis following the conventional features of good academic writings. The topical theme dominantly occupies the theme system chosen for the thesis. This study confirms that a good academic text shares its characteristics across cultures, suggesting that the teaching of academic writing in one culture could refer to the characteristics of good academic texts in other cultures.Â